Enzymatic treatments effect on the poly (butylene succinate)/date palm fibers properties for bio-composite applications - Chaari, Rania; Khlif, Mohamed; Mallek, Hanen; Bradai, Chedly; Lacoste, Catherine; Belguith, Hafedh; Tounsi, Hejer; Dony, Philippe (Industrial crops and products, 2020)
•Optimization of fibers treatment process was considered for date palm fibers.•Mechanical properties of date palm fibers filled composites were investigated.•Enzymes which are free of cellulases activities contributed to cellulose-rich fibers.•Biodegradable composites at low cost and high rigidity were obtained.•High potential of DPFs filled composites for industrial sustainability was revealed. In the context of raw materials valorization, reducing pollution and producing more energy, the world is undergoing a revolutionary shift towards biodegradable materials. Biosourced materials used for biocomposites gain more and more attention regarding different properties and are means of improving properties, especially mechanical ones. The aim of this research was to evaluate the effect of various enzymatic treatments (xylanase, pectinase and xylanase + pectinase) on chemical structures, morphology and mechanical properties of date palm fiber (DPF) and reinforced DPF composites. Two types of palm residues, namely: palm and trunk, were subject of several experiments. The reaction time of fiber-enzyme treatments and enzyme activities were optimized by measuring the liberated reduced sugar. The treatments effect on the fibers surface was also examined by a Scanning Electron Microscope. Different fiber contents and fiber treatments substantially improved mechanical properties (Tension and impact resistance). Results have shown that an enzyme treatment for 8 h is enough to liberate the maximum of amorphous components. The treatment combining pectinase + xylanase enzymes contributed to more fibrillose structures and proper surface which indicates an effective elimination of lignin, hemicellulose and extractive fractions. The palm variety exhibits relatively high values of cellulose compared to trunk fiber. It was found that enzymatically treated date palm fibers enhance the composite materials rigidity by about 42 % and 29 % for trunk and palm fibers, respectively. Sustainable products with such characteristics could enhance the development and progress of sustainable industries.